Review : Peranan Bakteri Pendegradasi Senyawa Pencemar Lingkungan melalui Proses Bioremediasi - Rida Oktorida Khastini; Laila Rahma Zahranie; Risma Aulia Rozma; Yolanda Ade Saputri (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2022)
Pollutants can cause pollution and poisoning of biotic components in a natural ecosystem in dangerous compounds such as hydrocarbons, mercury, ammonium nitrogen, and difficult-to-degrade plastics. Therefore, bioremediation is used to manage and control pollutants through bacteria. This article provides an overview of the latest information regarding bacteria as bioremediation agents and the technology's mechanisms. The method used is qualitative data breakdown by observing and drawing conclusions in the journal to examine the role of bacteria as bioremediation agents for harmful pollutants. Based on the study, bacteria have a unique metabolism to degrade inorganic and organic pollutants such as hydrocarbons (including petroleum), diesel oil, ammonia nitrogen, cellulose, starch, fat, styrofoam, chromium, and heavy metals. Furthermore, the overall environmental conditions can also help the organisms involved to accelerate the bioremediation process.